1987
DOI: 10.1063/1.339476
|View full text |Cite
|
Sign up to set email alerts
|

Transient photoconductivity measurements in semi-insulating GaAs. II. A digital approach

Abstract: We describe an experimental setup designed to study photoconductive transients in semi-insulating materials. The method, known as photoinduced transient spectroscopy, is based on a digital signal-averaging technique. Although this digital method eliminates or reduces many of the experimental problems encountered when using an analog approach, several new problems arise. The method is described, and the difficulties are illustrated using data obtained from both Cr-doped and nominally undoped samples of GaAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…This can in principle be remedied by increasing the high temperature in the DLTS temperature scan, but the leakage current of Schottky diodes or p-n diodes in GaN-based devices is usually relatively high even at room temperature which makes it very difficult to carry out reliable capacitance measurements at temperatures exceeding $500 K. Undoped III-Nitrides grow usually preferentially n-type, so minority carriers traps in such films had to be studied on Schottky diodes by the DLTS version with optical injection pulse, the so called optical DLTS (ODLTS) [2]. The as-grown, annealed or irradiated III-Nitrides are often semi-insulating and deep traps in them have to be detected by using the photoinduced current transient spectroscopy (PICTS or OTCS) which is similar to DLTS, but utilizes photocurrent relaxations induced by optical injection pulse [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This can in principle be remedied by increasing the high temperature in the DLTS temperature scan, but the leakage current of Schottky diodes or p-n diodes in GaN-based devices is usually relatively high even at room temperature which makes it very difficult to carry out reliable capacitance measurements at temperatures exceeding $500 K. Undoped III-Nitrides grow usually preferentially n-type, so minority carriers traps in such films had to be studied on Schottky diodes by the DLTS version with optical injection pulse, the so called optical DLTS (ODLTS) [2]. The as-grown, annealed or irradiated III-Nitrides are often semi-insulating and deep traps in them have to be detected by using the photoinduced current transient spectroscopy (PICTS or OTCS) which is similar to DLTS, but utilizes photocurrent relaxations induced by optical injection pulse [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have experienced similar problems with nonexponential behavior when they tried to fit transient conductivity from SI GaAs. 19,20 The underlying reason for nonexponential characteristics needs to be clarified, otherwise, the results from the best multiple exponential fitting procedures requiring as many as four or five emission rates have little physical meaning. 19 Here we propose one possible answer to the phenomenon of nonexponential transients.…”
Section: Discussionmentioning
confidence: 99%
“…This is analogous to digital transient photoconductivity measurements reported on such material. 18,19 Common practice is to assume that the near-surface conductance ͑or free-carrier concentration͒ is solely controlled by deep-level emission, and thus to fit the entire waveform to a simple exponential function. However, we found that the V oc Ϫ1 decay was not a simple exponential function.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis of the PICTS technique has been discussed by several authors [7,8]. It was recognized that the current decay curves may consist of more than one exponential due to the simultaneous emission of carries from more than one trap level.…”
Section: Introductionmentioning
confidence: 99%